Some Aspects of Water Relations and Nutrition in Eucalyptus Plantations - Ghosh, R. C.; Kaul, O. N.; Subba Rao, B. K. (Indian Forester, 1978)
This is a brief survey of the information available on the effects of Eucalytpus plantations with particular reference to water relation and soil nutrition. It appears that their benificial effects out-weigh any possible adverse effects and the complaints regarding the adverse effects of Eucalyptus plantations on water supply is rather exaggerated.